On the Nature of Clitics and Their Sensitivity to Number Attraction Effects - Santesteban, Mikel; Zawiszewski, Adam; Erdocia, Kepa; Laka, Itziar (Frontiers in Psychology, 2017)
Pronominal dependencies have been shown to be more resilient to attraction effects than subject-verb agreement. We use this phenomenon to investigate whether antecedent-clitic dependencies in Spanish are computed like agreement or like pronominal dependencies. In Experiment 1, an acceptability judgment self-paced reading task was used. Accuracy data yielded reliable attraction effects in both grammatical and ungrammatical sentences, only in singular (but not plural) clitics. Reading times did not show reliable attraction effects. In Experiment 2, we measured electrophysiological responses to violations, which elicited a biphasic frontal negativity-P600 pattern. Number attraction modulated the frontal negativity but not the amplitude of the P600 component. This differs from ERP findings on subject-verb agreement, since when the baseline matching condition obtained a biphasic pattern, attraction effects only modulated the P600, not the preceding negativity. We argue that these findings support cue-retrieval accounts of dependency resolution and further suggest that the sensitivity to attraction effects shown by clitics resembles more the computation of pronominal dependencies than that of agreement.